THE INFLUENCE OF COMPENSATION AND MOTIVATION ON EMPLOYEE PERFORMANCE IN PT ARWANA ANUGERAH KERAMIK TBK - Denny Nabawi; zunaidah zunaidah; kosassih zen (JEMBATAN, 2018)
This research purpose is to examine the effect of compensation and motivation on employee performance in PT Arwana Augerah Keramik Tbk. The object of this research is an employee in PT Arwana Anugerah Keramik Tbk. with 80 employees as a sample. Method for collecting data is using questionnaire. The collected data are tested by validity test, reliability test, analysis coefficient of determination test (R2), T Test (Partial), F test (Simultaneous) and Multiple Linear Regression Analysis. The result of this research indicate that compensation has a significant positive effect on employee performance with 2,603 > t table 1,668 where motivation aslo has a significant positive effect on employee performance with 1,840 > t table 1,668. Simultaneously, independent variable effect on employee performance with 0.761 or 76,1% influence on employee performance. Keywords : compensation, motivation, employee performance.